2009
DOI: 10.7150/ijms.6.77
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anal symptoms and anal findings

Abstract: Background: The frequencies and types of anal symptoms were compared with the frequencies and types of benign anal diseases (BAD). Methods: Patients transferred from GPs, physicians or gynaecologists for anal and/or abdominal complaints/signs were enrolled and asked to complete a questionnaire about their symptoms. Proctologic assessment was performed in the knee-chest position. Definitions of BAD were tested in a two year pilot study. Findings were entered into a PC immediately after the assessment of each in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 21 publications
0
19
0
2
Order By: Relevance
“…Therefore, recurrences with our patients seem rather unlikely but anal inflammation is supposable announced by itching (18.8%), pricking (10.4%), and a sore anus (8.3%). 24,25,28 Patient attitudes against our treatment policy did not influence therapeutic results since the majority of patients characterized it as "valuable to test" or "understandable" (61.1%). These patients had no better results than those who …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, recurrences with our patients seem rather unlikely but anal inflammation is supposable announced by itching (18.8%), pricking (10.4%), and a sore anus (8.3%). 24,25,28 Patient attitudes against our treatment policy did not influence therapeutic results since the majority of patients characterized it as "valuable to test" or "understandable" (61.1%). These patients had no better results than those who …”
Section: Discussionmentioning
confidence: 99%
“…In einer kürzlich publizierten Studie wurden über 800 Patienten mit analen und/oder gastrointestinalen Beschwerden befragt und untersucht [7]. Ein Pruritus bestand bei über der Hälfte der Patienten mit benignen analen Erkrankungen.…”
Section: Epidemiologieunclassified
“…2 Moreover concomitant anal findings were shown to play a role in the pathogenesis of benign anal diseases when patients with and without concomitant anal findings and benign anal diseases were compared (P  0.01). …”
Section: Figure 3amentioning
confidence: 99%
“…4 Others found that the lithotomy position seems to be less tolerated. 5 Whilst diagnoses might depend on positioning, 1,2 doctors argue that the patient's sense of shame is violated in other than the left lateral Sims' position. 4,5 In fact doctors might be biased regarding positioning of patients for proctological examination and some may even conceal their own preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation